Interface : creating a climate fit for life with carpet tiles - van Koert, Michelle; Sherwood, Deborah (London : Rotterdam School of Management, Erasmus University, 2019)
Carpet tile producer Interface has been a global frontrunner in becoming climate neutral. With its zero emissions targets within sight, Interface can't stop now: its new climate strategy pushes the frontiers of its sustainability journey, and it's calling on all stakeholders - internal and external - to join them in making it happen. But there are many unknowns out there and Interface must grapple with plans to go further and transition from climate neutral to carbon negative.
Originally Published Invan Koert, M., & Sherwood, D. (2019). Interface: Creating a Climate Fit for Life with Carpet Tiles. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sustainable development -- Case studies